PHARMACEUTICAL AND ANALYTICAL STANDARDIZATION OF MAHA SHANKHA VATI (International Journal of Ayurveda and Pharma Research, 2015)
Khalveeya Rasa is the combinations of herbal, mineral and animal products, so that we can have the effects of all collectively in a single formula. It preserve the properties of freshly added Churna, Swarasa etc., with the help of Moorchita Parada i.e., Kajjali, Rasashindura & Hingula etc. Because of which Khalveeya Rasaushadhies occupies greater portion in therapeutics as compare to other Kalpana, Such as Vati, Gutika, Taila, Ghrita. In the present study three sample of â€œMaha Shankha Vatiâ€ have been prepared by adopting method describe in Ayurvedic Formulary of India (A.F.I.) Vol. 2 approved by government of India with some desire changes.AIMS: The aim of this study is to prepare three sample of â€œMaha Shankha Vatiâ€ for its Pharmacoanalytical standardization. And also prepare â€œShankha Bhasmaâ€, â€œHingullotha Paradaâ€ and processing of last three Sanskara of Parada. Analytical Standardization of self made Maha Shankha Vati & market sample of Maha Sankha Vati to compare analytically.RESULT: After evaluating organoleptic characters of the first three samples of self made Maha Shankha Vati revealed black colored substance in the form of Vati having Amla-Katu Rasa, Amla smell and smooth touch having pH 3.39. Similarly in case of market sample (fourth sample) shows black in colored in the form of Vati with Lavan-Katu in Rasa, Amla Smell and smooth touch having pH 4.37. Further the XRD pattern analysis of the combined sample of Maha Shankha Vati, reveals the presence of HgS, Caco3, NaCl. Same observation found in market sample.